Edinburgh : the making of a capital city - Edwards, Brian, 1944-; Jenkins, Paul, 1953- (Edinburgh University Press, 2005)
This book provides a unique and comprehensive review of the making and re-making of Edinburgh over most of the last millennium. A series of themes of wide relevance are explored and discussed in the context of their impact upon the form of the city and its success as a capital. These include: The European influence on urban and architectural form. The synthesis of architecture, landscape and topography. The dialogue between conservation and innovation. The search for social, economic and cultural sustainability. The role of governance and public action in urban ecology. A special feature of the book is the way the Old and New Towns are discussed as a connected problem of image and politics, rather than two isolated events in the history of the city. Likewise, the relations between the city centre, the suburban edge and beyond throughout the 20th century are examined holistically, allowing the reader to gain a broader perspective both of the city of today and of the future. What emerges is a city unique - at least in the UK - in terms of the care taken over its image and sense of identity, and the political and institutional investment made in preserving this. Key Features: Deals with the development of the city in a holistic manner. Relates the physical evolution of the city to wide social, cultural, economic and political movements in the UK and Europe. Uses design, conservation, sustainability and governance as major structuring themes. Presents fresh perspectives on the making and re-making of Edinburgh over a period of nearly 1,000 years.